One Belt One Road Initiative: A Study through Economic Diplomacy Perspective - Pandey, Niha (KMC Research Journal, 2018)
With the third wave of globalization and information revolution, the demand for cross border relations has augmented. In international system, international relations have evolved significantly, which has created a demand to enhance relations among states. The relations among states are driven by Diplomacy. In addition, Diplomacy has always been a means or a tool to conduct international relations in order to achieve its national interest. With this note, this paper presents a study on One Belt One Road Initiative (OBOR) in relation to China’s Economic Diplomacy. The paper accommodates the major theoretical approaches of International Relations including Liberalism and Realism perspectives to precisely analyze China-led OBOR. The paper concludes by assessing the probabilities for future connectivity between South Asia and China.